(untitled) (International Journal of Adult Health Nursing, 2026)
Background: Aging populations are increasingly susceptible to malnutrition due to complex physiological, psychological, and social changes. Objective: To critically examine the role of nurses in geriatric nutritional management across care settings. Methods: An integrative review of current literature (2019–2025) was conducted using major databases, focusing on nursing roles in assessment, intervention, and monitoring. Results: Evidence indicates that nurse-led nutritional assessment using standardized tools significantly improves early detection of malnutrition. Interventions including dietary modification, feeding assistance, and patient education contribute to better clinical outcomes. Conclusion: Nurses play a pivotal role in optimizing nutritional status among older adults. Strengthening clinical competencies and interdisciplinary coordination is essential to address the growing burden of geriatric malnutrition.